Mediation effect of novelty ecosystems on intrapreneurial behaviour process within an organisational dynamic environment among Kenyan universities - Balunywa, J. Waswa (Emerald publishing company, 2017)
Purpose – The purpose of this paper is to examine, explain, predict and guide the processes, mechanisms and outcomes of intrapreneurial behaviour to provide evidence that novelty ecosystems mediate the relationships between generative influence, positive deviance and intrapreneurial behaviour. It also enlightens the capacity of replicating the intrapreneurial best practices. Design/methodology/approach – The study uses an integrated approach of entrepreneurship and complexity theories. Its subjects were full-time designated university employees in the Republic of Kenya. A total number of 244 employees were selected using snowball sampling technique from ten public and private universities in the Kenya. A self-administered questionnaire was used to collect data. Findings – The structural equation modelling path analysis and the bootstrapping results confirmed full mediation of novelty ecosystems in the relationship between generative influence and intrapreneurial behaviour. The findings, further, verified that novelty ecosystems partially mediate the relationship between positive deviance and intrapreneurial behaviour. Research limitations/implications – Subjective appraisals were used, despite the fact that studied variables are ultimately based on what employees perceive. Future research should generate and include more objective measures. Practical implications – Intrapreneurial behaviour can only be explained and predicted through novelty ecosystems. University leaders need to fully understand and facilitate novelty ecosystems. Social implications – A deeper understanding of the power of generative influence, positive deviance and novelty ecosystems will not be fully realized until researchers devote as much energy and attention to facilitation as has been devoted to conflict. Originality/value – This study extends existing intrapreneurial research into complexity approach.
: a complexity approach
Keywords: Complexity; Complex; Postive deviance; Intrapreneurial behavior; Generative influence; Novelty ecosystems